One reporter for in-cell activity profiling of majority of protein kinase oncogenes - Gudernova, Iva; Foldynova-Trantirkova, Silvie; Ghannamova, Barbora El; Fafilek, Bohumil; Varecha, Miroslav; Balek, Lukas; Hruba, Eva; Jonatova, Lucie; Jelinkova, Iva; Kunova Bosakova, Michaela; Trantirek, Lukas; Mayer, Jiri; et al. (eLife, 2017)
In-cell profiling enables the evaluation of receptor tyrosine activity in a complex environment of regulatory networks that affect signal initiation, propagation and feedback. We used FGF-receptor signaling to identify EGR1 as a locus that strongly responds to the activation of a majority of the recognized protein kinase oncogenes, including 30 receptor tyrosine kinases and 154 of their disease-associated mutants. The EGR1 promoter was engineered to enhance trans-activation capacity and optimized for simple screening assays with luciferase or fluorescent reporters. The efficacy of the developed, fully synthetic reporters was demonstrated by the identification of novel targets for two clinically used tyrosine kinase inhibitors, nilotinib and osimertinib. A universal reporter system for in-cell protein kinase profiling will facilitate repurposing of existing anti-cancer drugs and identification of novel inhibitors in high-throughput screening studies.
Keywords: in cell; protein kinase; Cell Line; activity; profiling; optické zobrazování; mouse; Cytological Techniques; proteinkinasy; Oncogene Proteins; cytologické techniky; receptor tyrosine kinase; human; reporter; cancer biology; Protein Kinases; Animals; lidé; onkogenní proteiny; Optical Imaging; zvířata; Humans; Intravital Microscopy; myši; buněčné linie; cell biology; Mice; intravitální mikroskopie